2002
DOI: 10.1038/sj.bjc.6600490
|View full text |Cite
|
Sign up to set email alerts
|

High resolution chromosome 3p, 8p, 9q and 22q allelotyping analysis in the pathogenesis of gallbladder carcinoma

Abstract: Our recent genome-wide allelotyping analysis of gallbladder carcinoma identified 3p, 8p, 9q and 22q as chromosomal regions with frequent loss of heterozygosity. The present study was undertaken to more precisely identify the presence and location of regions of frequent allele loss involving those chromosomes in gallbladder carcinoma. Microdissected tissue from 24 gallbladder carcinoma were analysed for PCR-based loss of heterozygosity using 81 microsatellite markers spanning chromosome 3p (n=26), 8p (n=14), 9q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 37 publications
(50 reference statements)
0
27
0
1
Order By: Relevance
“…Our finding of relatively frequent (24%) mutation at the D310 sequence in chronic cholecystitis without cancer supports the hypothesis that a subset of gallbladders with chronic inflammation may be at greater risk of progression to cancer. Of interest, in our previous studies similar frequencies of allele loss and genetic instability (24), gene aberrant methylation (35), and TP53 gene abnormalities 5 have been detected in chronic cholecystitis specimens. All of the epidemiological studies have shown that gallstones are the primary risk factor for GBC (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding of relatively frequent (24%) mutation at the D310 sequence in chronic cholecystitis without cancer supports the hypothesis that a subset of gallbladders with chronic inflammation may be at greater risk of progression to cancer. Of interest, in our previous studies similar frequencies of allele loss and genetic instability (24), gene aberrant methylation (35), and TP53 gene abnormalities 5 have been detected in chronic cholecystitis specimens. All of the epidemiological studies have shown that gallstones are the primary risk factor for GBC (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Because only a small fraction of patients with cholelithiasis and chronic cholecystitis develop gallbladder cancer (1) it is important to identify the factors that induce malignant progression. The development of epithelial cancer, including GBC (4,24,(33)(34)(35), requires multiple mutations. It is possible that those preneoplastic lesions that have accumulated multiple mutations are at higher risk for progression to invasive cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on mutations of dominant oncogenes (K-ras) or tumor suppressor genes (TSGs) [TP53, P16 INK4A , and FHIT (3)(4)(5)]. Genomewide and specific chromosome arm allelotyping analyses indicated that allelic losses at multiple sites of the genome are frequent in this neoplasm, suggesting the involvement of multiple TSGs in its pathogenesis (6,7). Recently, Hansel et al (8), using a RNA-based global gene expression microarray analysis of ϳ22,000 transcripts in a series of biliary tract tumors including 10 GBC specimens, detected a number of abnormally expressed genes, most of which had not been described previously in these tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…Hrk inactivation is also inversely correlated with apoptosis indices in tumors (17)(18)(19). Hrk is located in chromosome 12q13 (20) where loss of heterozygosity is often observed in several types of human tumors (21)(22)(23). Moreover, Hrk overexpression suppresses cell growth in prostate, breast, and ovarian cancer cells (24).…”
Section: Introductionmentioning
confidence: 99%